IMPLEMENTASI FATWA DSN MUI NO 75 TAHUN 2009 TENTANG PENJUALAN LANGSUNG BERJENJANG SYARIAHDI PT. MOMENT GLOBAL INTERNASIONAL - Joni Hendra (INTELIGENSIA MEDIA, 2023)
The writing of this thesis is based on the existence of a Multilevel Marketing business that has received a certificate from the National Sharia Board of the Indonesian Ulema Council (DSN-MUI), or also known as Sharia Tiered Direct Selling (PLBS). One of the MLMs that has received a certificate from the DSN-MUI is PT. Momen Global Internasional headquartered in Surabaya, assisted by branch offices in Jakarta and Makassar. This research uses qualitative research in the form of case studies. The approach used in this research is a case study. The method used by the author, namely the primary data source obtained from interviews from several parties of PT. Momen Global Internasional; a manager, a leader and a member. Secondary data sources in this study are more directed at supporting data such as DSN-MUI fatwas, journals, related books, and others. The results of this study state that: First, PT. Moment Global International is a Syariah Multilevel Marketing Company that sells nutrition supplement and health products , it has received a certificate from The Indonesian Ulema Council (MUI) The Motto is used in marketing their products are use it (Comsumtion),Love it (feeling the benefits) share it (telling the story )which the results will be profit ,none of which violates syariah in products sales ,giving bonuses or commissions to members has followed the guidelines in the DSN-MUI number 75 of 2009 concerning about Syariah tiered direct sales. Second, Overall, the practices that occur in PT. Momen Global Internasional are in accordance with the provisions of the DSN-MUI fatwa. Especially the 12 points that have been formulated by the DSN-MUI regarding the PLBS guidelines. The transaction contract of PT. Momen Global Internasional are bay’ contracts, wakalah bil ujrah contracts and ju'alah contracts. All contracts are in accordance with what has been formulated by DSN- MUI.